Brilliant Green and Acid Orange 74 Dyes Removal from Water by Pinus roxburghii Leaves in Naturally Benign Way: An Application of Green Chemistry. (11th March 2019) - Rehman, Rabia; Muhammad, Sara Jan; Arshad, Muhammad
Abstract : The purpose of this study was to use low cost and easily accessible biosorbent for batch-scale elimination of brilliant green and acid orange 74 dyes from aqueous solution. Pinus roxburghii leaves were utilized to study their dye-eliminating capacities. The adsorbent was characterized by FTIR, TGA, DTA, and SEM. The optimized conditions for brilliant green and acid orange 74 dye elimination were adsorbent dose, 1.2 and 1.8 g; contact time, 30 and 45 min; pH, 2 and 1; temperature, 50°C and 60°C; and agitation speed, 125 rpm and 50 rpm for BG and AO-74, respectively. Adsorption records well fitted Langmuir isotherm. Possibility of the procedure was shown by negative values of the thermodynamic parameter ∆G° for both dyes. Kinetic studies showed that adsorption of BG and AO-74 dyes from watery solution by PR leaves followed pseudo-second-order kinetics.